Implementation of ERP system in SMEs - Ahmed, Fahd Nazir (Cranfield University, 2009)
This thesis tries to propose a list of Critical Success Factors (CSFs) in the form of CSFs framework for Enterprise Resource Planning (ERP) system implementation at Small and Medium sized Enterprises (SMEs).The research describe in this thesis tries to test them by going through the experience of ERP system implementation in SME called Hazelwood Sound & Vision Ltd (HSV). In a first instance, the author compared implementation models and suggested most appropriate model for HSV. Furthermore, literature search for critical success factors of ERP implementation has taken place. This led to a general CSFs framework for ERP system implementation. At later stage, CSFs were classified into the phases of selected implementation model. This resulted in integrated framework which later used for ERP system implementation called Smart Office in HSV. Through this experience of implementing Smart Office in HSV, the author determined factors which were critical for the success of the ERP implementation in HSV and compared them with CSFs found in literature. The study also examines, through the critical success factors, the impacts and issues in implementation related to these factors. Findings include: an increased emphasis upon the determination of clear goals and objectives at the project outset, and, importantly, vendor support added value in terms of specialist software knowledge and enhanced project team capability. Results show that most of the success factors, found in the literature apply to HSV, although change management, and communication among departments, don‟t seems to be regarded as top CSFs for HSV. Implementation is an expensive investment, and difficult to implement, due to its complexity. It is hoped that knowledge and understanding of these factors will assist SMEs in successfully implementing ERP and enable them to further improve their systems in order to maximize returns. Furthermore, by identifying relevant CSFs for SMEs, managers can better prioritize implementation efforts and resources to maximize success of ERP implementations. One of the outcomes of this research is implementation of Smart Office which fulfils the business needs of the HSV.